Analysis of The Application of National Standards on Aspects of Human Resources in Special Libraries - Aprianinsi, Lini; Samosir, Fransiska Timoria; Sa'diyah, Lailatus (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
This research investigates the implementation of National Standards concerning the Human Resources Aspect in the Special Library of the Diplomatic Ministry of Foreign Affairs. The primary focus is on the roles and qualifications of human resources (HR) in library development. The study aims to determine the suitability of applying National Standards related to the Human Resources Aspect in the Special Library of the Diplomatic Ministry of Foreign Affairs and to understand the challenges that arise when the library faces a shortage of human resources (HR). This research employs a descriptive qualitative method involving observation, interviews, and documentation. It includes two librarians and two library technical staff members. The findings reveal that within the general standards, one out of three components remains unfulfilled. The qualification standard for the head librarian is entirely unmet due to the absence of a head librarian in the library. For the qualification standard for librarians, one out of three components remains unfulfilled. Similarly, for the qualification standard for library technical staff, two out of three components remain unmet. The human resources in the Diplomatic Ministry of Foreign Affairs Library do not meet all the standard components, resulting in an increased workload for the existing librarians, as they bear responsibility for all tasks within the library. The significance of this research is to find out the deficiencies that exist in the library and then to correct the deficiencies that exist in the library.